PENGARUH PERHATIAN ORANG TUA TERHADAP KREATIVITAS BELAJAR PESERTA DIDIK DI MTS MUHAMMADIYAH JULUBORI KECAMATAN PALANGGA KABUPATEN GOWA - Hanafy, Muhammad Sain; ., Nikawati (Inspiratif Pendidikan, 2017)
This study aims to obtain a description of the attention of parents of learners in MTs Muhammadiyah Julubori and creativity of learning in MTs Muhammadiyah Julubori and the influence of parents' attention on the creativity of learners in MTs Muhammadiyah Julubori. This type of research is quantitative research with ex-postfacto approach. The population in this study were all students in MTs Muhammadiyah Julubori Kecamatan Palangga Gowa District with the number of 131 people while the sample is 25% of all students in MTs Muhammadiyah Julubori as many as 33 students and their parents respectively so that the total sample to 66 taken through simple random sampling technique. The instrument used in this study is a questionnaire. The analysis technique used is descriptive statistical analysis and inferential statistical analysis with simple regression analysis technique. Based on the results of data analysis using descriptive statistics, then: (1) attitudinal attitude of parents learners obtained an average value of 33.64 are in the medium category, creativity learners learners obtained average value 28.64 is in the category of being, and the result of simple regression analysis between attitude of parents attention to creativity learners learn significant value> 0,05 (0,064) because significant value bigger than 0,05 hence can be concluded that attention of parent have no effect to creativity learn. Learning creativity is the potential of every learner, let every educational institution able to help learners to develop creativity that is owned well.